1992
DOI: 10.1091/mbc.3.3.249
|View full text |Cite
|
Sign up to set email alerts
|

Transcription on lampbrush chromosome loops in the absence of U2 snRNA.

Abstract: The five small nuclear RNAs (snRNAs) involved in splicing occur on the loops of amphibian lampbrush chromosomes and in hundreds to thousands of extrachromosomal granules called B snurposomes. To assess the role of these snRNAs during transcription and to explore possible relationships between the loops and B snurposomes, we injected singlestranded antisense oligodeoxynucleotides (oligos) against Ul and U2 snRNA into toad and newt oocytes. As shown before, antisense Ul and U2 oligos caused truncation of Ul and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 45 publications
2
28
0
Order By: Relevance
“…Interestingly, another component of the RNP matrix, the U1 snRNP, is normally detected in oocyte CBs by in situ hybridization at a level slightly higher than background levels obtained with control probes (42). Yet, upon truncation of its first 20 nucleotides, endogenous U1 accumulates in CBs (39). Because the splicing snRNPs traffic through CBs (27), one likely interpretation is that the exchange kinetics of U1 between CBs and the nucleoplasm are changed, resulting in an accumulation of U1 in CBs.…”
Section: Discussionmentioning
confidence: 93%
“…Interestingly, another component of the RNP matrix, the U1 snRNP, is normally detected in oocyte CBs by in situ hybridization at a level slightly higher than background levels obtained with control probes (42). Yet, upon truncation of its first 20 nucleotides, endogenous U1 accumulates in CBs (39). Because the splicing snRNPs traffic through CBs (27), one likely interpretation is that the exchange kinetics of U1 between CBs and the nucleoplasm are changed, resulting in an accumulation of U1 in CBs.…”
Section: Discussionmentioning
confidence: 93%
“…This positional relationship between sites of transcription and sites of pre-mRNA splicing is supported by a large body of observations at the light and electron microscope level (reviewed in Gall, 1992;Spector, 1993;Xing and Lawrence, 1993;Kramer et al, 1994). In some cases, the pre-mRNAs that are found associated with splicing components in these nuclear sites are in a nascent form (Beyer and Osheim, 1988;Gall and Callan, 1989;Vazques-Nin et al, 1990;Wu et al, 1991;Tsvetkov et al, 1992;Jimenez-Garcia and Spector, 1993;Wansink et al, 1993;Xing and Lawrence, 1993;Zachar et al, 1993). In other cases, the premRNA is found at various stages of the RNA processing pathway (Fakan et al, 1984;Carter et al, 1991;Xing and Lawrence, 1993;Kramer et al, 1994).…”
Section: Introductionmentioning
confidence: 88%
“…Transcription was inhibited by incubating pieces of ovary in actinomycin D (20 mg/mL) in OR2 medium. Splicing was inhibited by injecting individual oocytes with a single-stranded deoxyoligonucleotide complementary to part of the U2 snRNA molecule (Tsvetkov et al 1992). …”
Section: Animals and Oocytesmentioning
confidence: 99%
“…Earlier experiments showed that Xenopus oocytes can be depleted of U2 by injecting a specific antisense deoxyoligonucleotide . The snRNA is reduced to <1% of its original amount within 10-30 min and remains at this level for at least 48 h (Tsvetkov et al 1992). Under these conditions, splicing does not occur, and the normally abundant U2 snRNA is not detectable on the lampbrush chromosome loops by in situ hybridization.…”
Section: Nuclear Intronic Sequences Are Unusually Stablementioning
confidence: 97%
See 1 more Smart Citation